(untitled) (Journal of Ideas in Health, 2020)
With the escalating number of covid-19 positive cases and amidst the glooming shadows of an anticipated second wave of the covid-19 pandemic, the health care system of a developing country like India is already under pressure. With the encroachment of monsoon season, the ghosts of the past haunt India. Monsoon brings along endemic diseases like dengue, malaria, swine flu, Japanese encephalitis, chikungunya, etc. Every year there is significant morbidity and mortality. These diseases have clinical features of fever, sore throat, and body aches in common, which also happens to be the common manifestations of covid-19. The growing stigma related to COVID-19, the fake news, and fear related to hospitalization and isolation may lead to low reporting cases to the hospitals. Lockdown and non-availability of beds may perplex the situation further. There is an urgent need of the hour to address this grave issue to prevent a major mishappening. A comprehensive evaluation of the health-care systems is desperately needed, especially on the fronts of governance, decision making, scientific and technical advice, and operational capacity.